2018
DOI: 10.1007/s00401-018-1862-7
|View full text |Cite
|
Sign up to set email alerts
|

Convective influx/glymphatic system: tracers injected into the CSF enter and leave the brain along separate periarterial basement membrane pathways

Abstract: Tracers injected into CSF pass into the brain alongside arteries and out again. This has been recently termed the “glymphatic system” that proposes tracers enter the brain along periarterial “spaces” and leave the brain along the walls of veins. The object of the present study is to test the hypothesis that: (1) tracers from the CSF enter the cerebral cortex along pial-glial basement membranes as there are no perivascular “spaces” around cortical arteries, (2) tracers leave the brain along smooth muscle cell b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
268
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(285 citation statements)
references
References 39 publications
13
268
0
4
Order By: Relevance
“…It has also been shown that the majority of Ab removal (85%) occurs via the BBB and only a minority via ISF bulk flow in mice [72,73], and similar findings are reported from humans [74]. An intriguing notion is that the perivascular fibroblasts reside between the two basement membranes-the astrocyte-derived pial basement membrane and the basement membrane embedding the arteriolar and arterial VSMC-implicated in inward (arachnoid-to-brain) and outward (brain-to-arachnoid) tracer transport, respectively, indicating a possible role for the perivascular fibroblasts in the separation and compartmentalization of these tightly apposed transport routes [70]. Do pericytes play a role in the glymphatic system?…”
Section: Paravascular Flowsupporting
confidence: 69%
See 1 more Smart Citation
“…It has also been shown that the majority of Ab removal (85%) occurs via the BBB and only a minority via ISF bulk flow in mice [72,73], and similar findings are reported from humans [74]. An intriguing notion is that the perivascular fibroblasts reside between the two basement membranes-the astrocyte-derived pial basement membrane and the basement membrane embedding the arteriolar and arterial VSMC-implicated in inward (arachnoid-to-brain) and outward (brain-to-arachnoid) tracer transport, respectively, indicating a possible role for the perivascular fibroblasts in the separation and compartmentalization of these tightly apposed transport routes [70]. Do pericytes play a role in the glymphatic system?…”
Section: Paravascular Flowsupporting
confidence: 69%
“…In the glymphatic system, astrocytes are important for ion buffering and fluid exchange between the CSF and ISF, and it has been proposed that glymphatic clearance is higher in the sleep state [61]. Tracer flow does not connect to perivenous drainage, and studies of the routing of tracers show that tracers injected into the CSF enter along pial-glial membranes but exit the brain along VSMC basement membranes, going against the direction of blood flow [70]. The exchange through the glymphatic system has been suggested to be dependent on the water channel aquaporin-4 (Aqp4) present in the astrocytic endfeet ( Fig 3A).…”
Section: Paravascular Flowmentioning
confidence: 99%
“…Thus, quantifications of tracer that are performed within the PVS or parenchyma of the brain ex vivo are likely overestimates of the levels that are present in vivo. This phenomenon may also account for some of the previous findings based on ex vivo assessments that have concluded that CSF influx was occurring into the brain within minutes of tracer administration [2, 8, 45, 52]. …”
Section: Discussionmentioning
confidence: 55%
“…After a small skin incision over the occipital bone/cervical spinal cord was made, the three covering muscle layers were carefully dissected under a stereomicroscope using fine forceps and scissors. A beveled glass capillary micropipette (Sutter instruments, Novato, CA, USA) with a diameter of < 60 μm was made using a Sutter P97 Pipette puller (Sutter instruments) and was positioned perpendicular to the ear bars and advanced to penetrate the dura until resistance was overcome, indicating entry into the cisterna magna as previously described [2]. Overall, 5 µL of a Gadospin D solution at 25 mM gadolinium (nanoPET Pharma GmbH) was infused at the speed of 1 µL/min with a NanoJet syringe pump (Chemyx).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, PVMs may help control the velocity of IPAD through regulating VSMC constriction and relaxation. Of note, the velocity of IPAD is much slower in aged mice …”
Section: Pvm Functions In the Normal Brainmentioning
confidence: 97%